Differences Effectiveness Premature Infant Oralmotor Intervention (PIOMI) And Oromotor Stimulation (OMS) To Readiness Oral Feeding - Sumarni - Sumarni; Titin Sutini; Rohadi Hariyanto (UIMA Press, 2021)
Introduction: Premature birth is one of the biggest contributors to neonatal mortality and morbidity. It is difficult for premature infants to adapt to life outside the womb due to the immaturity of various organ systems, one of which is the suction reflex relevant to the readiness to oral feeding. Difficulty in oral feeding due to the weakness of sucking is a concern since it often delays the discharge of the infants from the hospital, negatively affects the relationship between mother and infants, and potentially causes eating disorders in children. Some of these reasons are the basis for early intervention to improve oral feeding ability. Interventions that can be carried out are PIOMI and OMS interventions. Objectives: This research aimed at identifying the differences in effectiveness between PIOMI and OMS with respect to the readiness of premature infants to oral feeding in the perinatology division of KMC Hospital, Luragung. Methods: The method used was a quasi-experimental research with pretest and posttest using a number of samples (N) = 32 respondents divided into two intervention groups respectively consisting of 16 respondents. Results: The results indicated that PIOMI (Δ = 9.0, p-value = 0.000) and OMS (Δ = 7.3, p-value = 0.000) had an effect on the readiness of premature infants to oral feeding. PIOMI intervention had a greater difference that consequently, it was more effective than OMS intervention. The confounding factors affecting the readiness of premature infants to oral feeding were gestational age and body weight, while chronological age did not affect. Conclusion: Based on the research results, it was suggested that nurses can use PIOMI intervention to make premature infants ready for oral feeding.